Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan (Studi Empiris pada Perusahaan yang Terdaftar di Indeks SRI-KEHATI Bursa Efek Indonesia) - Gema Bangun Djaya Atmadja; Ririn Irmadariyani; Novi Wulandari (UPT Penerbitan Universitas Jember, 2019)
This research aim to discover and analysis the effect of corporate social responsibility disclosure to corporate financial performance based on accounting measurement proxy with return on equity and corporate financial performance based on market measurement proxy with tobin’s-q. Measurement of corporate social responsibility disclosure based on guidelines disclosure of global reporting initiative generation four (GRI-G4). Research population that been used was all companies that listed in SRI-KEHATI index of Indonesia Stock Exchange in 2013-2016 period. Research sample consisted of 19 companies selected using purposive sampling method from 33 companies listed in SRI-KEHATI index of Indonesia Stock Exchange. Data that was used are companies annual report and stock price obtained from Indonesia Stock Exchange website as well as the website of companies that became sample. Hypothesis testing method that been used was simple regression analysis. The research result showed that corporate social responsibility disclosure are not proven to have an effect on corporate financial performance, either financial performance based on accounting measurement and financial performance based on market measurement. Keywords: Corporate Social Responsibility, Financial Performance, SRI-KEHATI Index